Knowledge, attitude and practice towards salt intake and health among non-academic staff of Universiti Kebangsaan Malaysia: A pilot study - Ismail, Munirah; Regu, Tuneesha; Jimponey, Martha James; Michael, Viola; Mohamed, Fathimah Nestha; Hussin, Rohana; Mat Ludin, Arimi Fitri (Life Sciences, Medicine and Biomedicine, 2021)
Background: Over the years, global salt intake has increased and has resulted in the escalation of cardiovascular diseases and hypertension. The lack of knowledge, as well as poor attitude and practice, are the main reasons that have led to high salt intake. Therefore, this study aims to evaluate the knowledge, attitude and practice (KAP) towards salt intake and health among non-academic staff of the Faculty of Health Sciences (FSK), Universiti Kebangsaan Malaysia (UKM). Methodology: This cross-sectional study was conducted among the non-academic staff of the Faculty of Health Sciences (FSK), Universiti Kebangsaan Malaysia (UKM). The respondents were recruited using stratified random sampling technique with an informed consent. A validated questionnaire to test the knowledge, attitude and practice (KAP) towards salt intake and health by the Ministry of Health Malaysia was converted into a Google form and the link was emailed to 118 participants. A total of 33 responses were obtained for evaluation. The significant values were set as P < 0.05. Results: It was observed that female participants had better attitudes towards salt intake and health compared to males (p = 0.044). Also, individuals with higher education levels had better attitudes towards salt intake and health, compared to those with lower education levels (p=0.009). However, knowledge and practice of salt intake and health bore no significant results when considering gender, education level and age. Discussion and Conclusion: Overall, this study has identified sociodemographic characteristics as contributing factors towards individuals’ attitude on salt intake and health. This may provide a crucial foundation in the development of cost-effective healthcare programs to widen knowledge, create awareness and promote a healthy lifestyle by reducing salt intake and further reduce the prevalence of non-communicable diseases.